Efficacy Comparison between Laser Lithotripsy (LL) and Pneumatic Lithotripsy (PNL) for Distal Ureteric Calculi - Bamroongya, Manit (Journal of Health Science of Thailand, 2017)
The objective of this study was to compare the efficacies and complications of Laser Lithotripsy (LL) and Pneumatic Lithotripsy (PNL) in the treatments of distal ureteric calculi by ureterorenoscopic techniques for patients admitted to the hospital in a prospective randomized controlled trial. They underwent either control trial ureterorenoscopic technique auxillary with ureteric fragmentation Laser Lithotripsy (LL) or Pneumatic Lithotripsy (PNL) depending on surgical indications. Patients were all randomized by labeled case by case, proceeded to under go surgical procedure either by spinal or general anaesthesia. Statistical analyse of surgical results were conducted by comparing of stone free rates and complications of both surgical techniques. From May 31, 2012 to January 7, 2013, 84 patients were enrolled into this study. While 42 patients underwent Laser Lithotripsy and the others 42 patients with Pneumatic Lithotripsy. Overall efficacy of both techniques in stone free rate were not statistically different 97.62 percent of Laser Lithotripsy and 92.86 percent by Pneumatic Lithotripsy. Nevertheless complications of Pneumatic Lithotripsy were higher in multiple aspects of 19.05 percent stone retropulsion, 21.43 percent requiring auxillary introduced double - J ureteric stent insertion, 2.38 percent urosepsis and 2.38 percent incidentally sustained severe postoperative pain. In conclusion, Laser Lithotripsy and Pneumatic Lithotripsy were not different in efficacy of stone fragmentation but serious complications were found higher in the Pneumatic Lithotripsy group.